2001
DOI: 10.1086/320242
|View full text |Cite
|
Sign up to set email alerts
|

Multifractal Scaling, Geometrical Diversity, and Hierarchical Structure in the Cool Interstellar Medium

Abstract: Multifractal scaling (MFS) refers to structures that can be described as a collection of interwoven fractal subsets which exhibit power-law spatial scaling behavior with a range of scaling exponents (concentration, or singularity, strengths) and dimensions. The existence of MFS implies an underlying multiplicative (or hierarchical, or cascade) process. Panoramic column density images of several nearby star-forming cloud complexes, constructed from IRAS data, are shown to exhibit such multifractal scaling, whic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
84
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(91 citation statements)
references
References 73 publications
7
84
0
Order By: Relevance
“…If the perimeter-area dimension of a projected 3D structure is the same as the perimeter-area dimension of a slice, then the ISM value of ∼ 1.4 for projected contours is consistent with analogous measures in laboratory turbulence (Sreenivasan 1991). Chappell & Scalo (2001) determined the multifractal spectrum, f (α), for column density maps of several regions constructed from IRAS 60 µ and 100 µ images. The parameter α is the slope of the increase of integrated intensity with scale, F (L) ∝ L α .…”
Section: Diagnostics Of Turbulence In the Dense Interstellar Mediummentioning
confidence: 69%
“…If the perimeter-area dimension of a projected 3D structure is the same as the perimeter-area dimension of a slice, then the ISM value of ∼ 1.4 for projected contours is consistent with analogous measures in laboratory turbulence (Sreenivasan 1991). Chappell & Scalo (2001) determined the multifractal spectrum, f (α), for column density maps of several regions constructed from IRAS 60 µ and 100 µ images. The parameter α is the slope of the increase of integrated intensity with scale, F (L) ∝ L α .…”
Section: Diagnostics Of Turbulence In the Dense Interstellar Mediummentioning
confidence: 69%
“…They found that regions with the highest sonic Mach number lie around the bar. Chappell & Scalo (2001) arrived at a similar conclusion using a multifractal spectrum analysis of low-mass star-forming cloud complexes: there is little correlation between the geometrical properties of the gas and the level of internal SF.…”
Section: Power Spectral Index Versus Sfmentioning
confidence: 81%
“…For a bi-dimensional image 0 ≤ α q ≤ 2, where α q = 0 in the case of a sharp spike and α q = 2 for a homogeneous image. Therefore, low values of α q indicate denser regions, while high values indicate more rarefied regions, and the value of α q describes the degree of "spikiness" of an image (Chappell & Scalo 2001). The set of points of the domain with the same value of α q has fractal dimension F(α q ).…”
Section: Fractal and Multifractal Indicatorsmentioning
confidence: 99%